THE FUNCTIONS OF “ÇI” SUFFIX IN KYRGYZ AND TUVINIAN - Fatih ÇELİK (Fırat University, 2019)
Noun making “ÇI” suffix whose origin dates back to the old Turkish is encountered in all Turkish dialects together with “ÇU” suffix. It is seen that the suffix is commonly used and has a very vibrant structure. In this study, the areas of usage and meaning of this suffix in Kyrgyz and Tuvinian will be examined comparatively in terms of meaning it adds to words in those languages. While doing our analyzes, words in Kygyz and Tuvinian dictionaries will be studied and the mentioned suffix will be found and then be classified in terms of meaning it adds to words. The similarities and differences in the usage of the suffix will be introduced in two languages. During the course of study, examples will be given in different Turkish languages as well.